2018
DOI: 10.1002/psp.2141
|View full text |Cite
|
Sign up to set email alerts
|

Can the trailing spouse phenomenon be explained by employer recruitment choices?

Abstract: It is well known that couples tend to relocate for the sake of the man's career rather than the woman's, also known as the “trailing spouse phenomenon.” The role of employer choices in this process is unknown however. If employers are hesitant to make job offers to women who live a long way from the workplace (e.g., because of work–family balance concerns or a perceived risk that they will not follow through on their applications, or stay hired if employed), this tendency might constitute an underlying mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…In addition, under a life course perspective, it would also be possible to account for the specific roles of love and emotions for understanding decisions of couples (Collins, Welsh, & Furman, 2009) as well as for societal change and changing social values (Smits, Mulder, & Hooimeijer, 2004). It is also possible to include aspects of family obligations beyond the partner relationship (e.g., care of parents; e.g., Baldassar & Wilding, 2014) as well as possible discrimination effects by employers (Brandén, Bygren, & Gähle, 2018). Thus, a combined approach including human capital and bargaining arguments, aspects of gender roles, as well as the dynamic life course perspective seems to be the most promising conceptualisation for future migration research in general and for analysing migration patterns of internationally mobile couples in particular.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, under a life course perspective, it would also be possible to account for the specific roles of love and emotions for understanding decisions of couples (Collins, Welsh, & Furman, 2009) as well as for societal change and changing social values (Smits, Mulder, & Hooimeijer, 2004). It is also possible to include aspects of family obligations beyond the partner relationship (e.g., care of parents; e.g., Baldassar & Wilding, 2014) as well as possible discrimination effects by employers (Brandén, Bygren, & Gähle, 2018). Thus, a combined approach including human capital and bargaining arguments, aspects of gender roles, as well as the dynamic life course perspective seems to be the most promising conceptualisation for future migration research in general and for analysing migration patterns of internationally mobile couples in particular.…”
Section: Discussionmentioning
confidence: 99%
“…The context-level normative beliefs and structural opportunities in which these decision-making processes are embedded need to be addressed as well. Recent research has tackled some of these contextual factors, including occupational conditions (Shauman and Noonan 2007;Benson 2014), sex-typed occupations (Perales and Vidal 2013), employment discrimination (Brandén, Bygren, and Gähler 2018), social relationships (Mulder 2007;Coulter, van Ham, and Findlay 2016), regional socioeconomic structures (Nisic 2010;Zaiceva 2010;Nisic and Melzer 2016), and welfare institutions and gender cultures (Boyle et al 2001;, among others.…”
Section: Gender Inequality In Couple-household Mobilitymentioning
confidence: 99%
“…Research in these areas has repeatedly pointed out that geographical mobility is primarily beneficial to the careers of men and often disadvantages the careers of women in a couple (Amcoff & Niedomysl, 2015;Känsälä et al, 2015;Valcour & Tolbert, 2003;Van der Klis & Mulder, 2008). Numerous studies have shown how the 'distinct gender dynamics' (Jöns, 2011) that mobility displays, disadvantage womenboth in terms of access to short-term as well as longterm mobility (e.g., Brandén, Bygren, & Gähler, 2018;Lee, Chua, Miska, & Stahl, 2017;Varma & Russell, 2016;Wheatley, 2013)especially when they have children (Guillaume & Pochic, 2009;Waibel, Aevermann, & Rueger, 2018). Due to these observations and the fact that women tend to work closer to their home to enable them to fulfil their household responsibilities, they have been described as 'spatially entrapped' (Wheatley, 2013, p. 720).…”
Section: The Gender Ordermentioning
confidence: 99%